Awaken the Awareness of Transcendence: New Strategies for Catholic Schools in the Netherlands to Deal with Secularization - van der Zee, Theo (Verbum Vitae, 2024)
Secularization poses serious challenges for religiously affiliated schools. Catholic schools in the Netherlands find themselves embarrassed regarding their educational endeavor because they are unable or lack the inspiration to talk about this subject in religious terms. This article aims to explore new ways of overcoming this embarrassment. Firstly, an overview is presented of the current situation and of the embarrassment of Catholic schools, in terms of their problematic choice of actions. Based on a critical-dialogical convergence of theological and pedagogical considerations, a Catholic vision on the educational endeavor is subsequently developed that is understood in terms of interruption, the other, and transcendence. From this vision of the educational endeavor, new strategies are presented – at the community level of Catholic schools, and at the individual level of teachers, school leaders, and governors – to promote an openness to receiving new, unexpected insights and possibilities. The receipt of these insights and possibilities is closely related to an awareness of transcendence, in both a secular and a religious sense. The initial findings of recent empirical research on the impact of these strategies are presented.